2018
DOI: 10.1021/acs.cgd.8b00783
|View full text |Cite
|
Sign up to set email alerts
|

London Dispersion Forces in Crystal Packing of Thiourea Derivatives

Abstract: Novel thioureas RNHC­(S)­NHP­(S)­(OiPr)2 [R = (HOCH2)­(Me)2C (1), Me2CH2CH2 (2), 2-CF3C6H4 (3), 2-Pym (4), and bis-thiourea 1,5-C10H6{NHC­(S)­NHP­(S)­(OiPr)2} (5)] have been synthesized and characterized by NMR, X-ray diffraction, Hirshfeld surface analysis, and theoretical ETS-NOCV charge and energy decomposition calculations. The monomers contain multiple intramolecular noncovalent interactions including N–H···X (X = O, 1–3; F, 3; N, 4; S, 5) and C–H···Y (Y = O, 1; N, 2 and 3; S, 4 and 5) augmented further b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 107 publications
(202 reference statements)
2
18
0
Order By: Relevance
“…Particularly, ΔE dispersion is extremely significant at absolute level; it is −141 kJ mol −1 for 2 and − 144 kJ mol −1 for 1 ( Table 2). It is in accord with the recent findings which highlight that bulky substituents might lead to enhancement of the molecular stability since their London dispersion donating properties might easily outweigh the corresponding steric (Pauli/kinetic) repulsion [59][60][61][62][63][64]. In the forthcoming paragraphs, electron density reorganization channels due to formation of various types of non-covalent interactions are identified and discussed in detail.…”
Section: Ets-nocv Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…Particularly, ΔE dispersion is extremely significant at absolute level; it is −141 kJ mol −1 for 2 and − 144 kJ mol −1 for 1 ( Table 2). It is in accord with the recent findings which highlight that bulky substituents might lead to enhancement of the molecular stability since their London dispersion donating properties might easily outweigh the corresponding steric (Pauli/kinetic) repulsion [59][60][61][62][63][64]. In the forthcoming paragraphs, electron density reorganization channels due to formation of various types of non-covalent interactions are identified and discussed in detail.…”
Section: Ets-nocv Analysissupporting
confidence: 84%
“…The former involves charge transfer from the lone pair of chlorine to the empty σ*(C-H), whereas the latter consist of donation from σ(C-H) to the empty π* of phenyl ring. Additionally, homopolar dihydrogen close contacts CH … HC lead to the two ways charge delocalization channels σ(C-H)➔ σ*(C-H) (and vice-versa) [61][62][63][64]. They all amount to ΔE orb (4 + 5 + 6) = −14 kJ mol −1 (Fig.…”
Section: Ets-nocv Analysismentioning
confidence: 99%
“…The prevalence of the DE disp term is consistent with recent ndings, which rediscover the importance of London dispersion forces in small and sizeable species. 24,27,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] In 3 the [Zn(NCS) 4 ] 2À anion sticks very strongly (DE int ¼ À193.21 kcal mol À1 ) to two neighboring stacked [Zn(NCS)L II ] + units primarily through electrostatic forces (75.3% of the overall stabilization) (Fig. 5).…”
mentioning
confidence: 99%
“…In order to evaluate aromaticity in 1-3, we have applied the electron density of delocalized bonds (EDDB) method, which has been proposed to visualize and quantify aromaticity and chemical resonance in a wide range of chemical species. [57][58][59][60] Moreover, it has recently been shown that, in the case of organometallics, the EDDB method provides very useful data on the role of the transition metal d-orbitals in electron delocalization, 24,27,50,61 which is inaccessible by means of such popular and commonly used aromaticity descriptors as the nucleusindependent chemical shi (NICS) 62 or the anisotropy of the induced current density (ACID). 63 The global EDDB isocontours and the corresponding electron populations of 1-3 are collected in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation